Black Resonance : Iconic Women Singers and African American Literature - Lordi, Emily J., 1979- (Book collections on Project MUSE., 2013)
"Ever since Bessie Smith's powerful voice conspired with the "race records" industry to make her a star in the 1920s, African American writers have memorialized the sounds and theorized the politics of black women's singing. In Black Resonance, Emily J. Lordi analyzes writings by Richard Wright, Ralph Ellison, James Baldwin, Gayl Jones, and Nikki Giovanni that engage such iconic singers as Bessie Smith, Billie Holiday, Mahalia Jackson, and Aretha Franklin. Focusing on two generations of artists from the 1920s to the 1970s, Black Resonance reveals a musical-literary tradition in which singers and writers, faced with similar challenges and harboring similar aims, developed comparable expressive techniques. Drawing together such seemingly disparate works as Bessie Smith's blues and Richard Wright's neglected film of Native Son, Mahalia Jackson's gospel music and Ralph Ellison's Invisible Man, each chapter pairs one writer with one singer to crystallize the artistic practice they share: lyricism, sincerity, understatement, haunting, and the creation of a signature voice."--Publisher website